P01.154 Volumetric response to TTFields in newly diagnosed GBM - Kerschbaumer, J (Neuro Oncol, 2018)
BACKGROUND: Optune TTField treatment is an established, non-invasive therapy for patients with newly diagnosed or recurrent glioblastoma (GBM). Treatment efficacy was evaluated demonstrating significant improvement of both, overall and progression free survival. For analysis, the MacDonald criteria were used in clinical practice as well as in the EF-14 trial. We performed a 3D volumetric analysis of patients with newly diagnosed GBM who underwent resection and chemoradiation plus TTFields additionally. MATERIAL AND METHODS: Between February 2016 and April 2017, 14 patients were initiated with TTField treatment. Seven patients with a treatment duration of more than 3 months were available for analysis of volumetric response rates (newly diagnosed GBM, device usage over 60%). Patients included were using the device between 3 and 14 months. A 80% cutoff in device usage was arbitrary set as this corresponds to the recommended daily usage of over 18 hours (= 75% ADU). Contrast enhancing tumor on T1 imaging (MPRAGE, 1mm slice thickness) was assessed by segmentation and volumetric analysis. RESULTS: The median age was 48 years (range 17–68 years) at the date of treatment initiation. Median preoperative tumor volume was 20.3 cc (range: 1.12–58.6cc), postoperative volume was 6.3 cc (range: 0–14.2cc) and volume at time of analysis was 1.2 cc (range: 0–7.1cc). Average device usage (ADU) of these patients was 89.5%. The median change of volume from postoperative to posttreatment volume was 4cc (range: 0–7.1cc) in patients with a median device usage of over 80%; whereas in patients with lesser than 80%, the mean volume change was 2.2cc (range 0–3.2cc). CONCLUSION: TTFields are generally accepted and efficacious for treatment of GBM. Our analysis showed that the combination of radiation, Temozolomide and TTFields lead to a reduction in contrast enhancing tumor volume. The effect seems to be related to treatment duration.